Penerapan Metode Simple Moving Average (SMA) dalam Peramalan Penjualan guna Menentukan Persediaan Optimal di Rumah Jahit RiBi - Marsono; Masrurotur Rodiyah; Ithrotul Farach; Rita Amelina Sholiha; Umi Nadhiroh (Shofanah Media Berkah, 2026)
This study aims to apply the Simple Moving Average (SMA) method in sales forecasting to determine the optimal level of raw material inventory at Rumah Jahit RiBi. The problem faced by this business is the fluctuation in demand for sewing services that causes inaccuracy in inventory management, thus potentially causing excess or shortage of raw materials. This study uses a quantitative approach with a quantitative descriptive design. The data used is historical data on sewing service sales for one year obtained through documentation and interviews with the business owner. The analysis method used is the Simple Moving Average to forecast sales in the next period. The results of the study show that the SMA method is able to produce more stable sales forecasts compared to actual data which is fluctuating. The forecast results can be used as a basis for determining raw material inventory needs in a more planned and efficient manner. Thus, the application of the SMA method can help Rumah Jahit RiBi in optimizing inventory management, reducing the risk of excess stock, and minimizing raw material shortages that can hamper the production process.